Management of public policy for celerity up child support proceedings in the peruvian judiciary - Fernández Espinoza, William Homer (2021)
The objective of this research is to verify if through the management of public policy it will be possible to comply in a timely manner with the processes of child support in the courts of peace of the judicial districts of the country. For its development, the doctrine was analyzed and field work was conducted through surveys directed to judges of the courts of peace of the Superior Court of Justice of North Lima, due to the good practices that this judicial district has been carrying out and because it obtained the ISO 9001:2015 certification for the implementation of a quality management system in attention to the processes of child support. Regarding the research methodology, this is descriptive and correlational; and the method applied is the inductive and quantitative and qualitative approaches. From the study of the results obtained, it is concluded that there is a process management system for the celerity of processes of child support claims, established in the objectives of the National Plan for Access to Justice for Persons in Condition of Vulnerability 2016-2021, but it is not met, due to various factors related to the insufficiency of economic, technological, material and human resources in the judiciary.